1991
DOI: 10.1073/pnas.88.19.8367
|View full text |Cite
|
Sign up to set email alerts
|

The position of the microtubule-organizing center in directionally migrating fibroblasts depends on the nature of the substratum.

Abstract: Immunofluorescence and confocal microscopy were used to monitor the positioning of microtubuleorganizing centers (MTOCs) during directional migration of chicken embryo fibroblasts on planar substrata and within three-dimensional collagen gels. Homologous assay conditions based on the radial emigration of cells from cell aggregates were used in both cases. Whereas =70% of the cells migrating directionally on glass and at least 60% on other planar substrata have their MTOCs anterior to the nucleus, MTOCs are ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 21 publications
1
25
1
Order By: Relevance
“…However, mixed front-back positions have been observed in CHO cells during wound healing (Yvon et al, 2002), in endothelial cells under shear stress (Coan et al, 1993) and in fibroblasts grown on grooved substrates or grown in collagen gels (Schütze et al, 1991). These results challenge the view that the Golgi complex -similar to the centrosome -is always at the leading edge of a migratory cell.…”
Section: Introductioncontrasting
confidence: 55%
“…However, mixed front-back positions have been observed in CHO cells during wound healing (Yvon et al, 2002), in endothelial cells under shear stress (Coan et al, 1993) and in fibroblasts grown on grooved substrates or grown in collagen gels (Schütze et al, 1991). These results challenge the view that the Golgi complex -similar to the centrosome -is always at the leading edge of a migratory cell.…”
Section: Introductioncontrasting
confidence: 55%
“…Our experiments tested the hypothesis that directional migration requires that fibroblasts reorient in the direction of movement, as they do during spontaneous or wound-healing migration (Palazzo et al, 2001b;Ueda et al, 1997). MTOC reorientation does not occur in fibroblasts migrating within three-dimensionally oriented collagen gels (Schutze et al, 1991) or in wound-healing Journal of Cell Science 117 (8) (b) show that most PAK4 transfectants were flatter and more bipolar than controls, in which 20-25% of cells appear spherical before EF application. Primary fibroblasts from mouse embryos whose PAK4 expression was knocked out by homologous recombination (PAK4 -/-; c) and PAK4-expressing heterozygotes (PAK4 +/-; d) were morphologically indistinguishable.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MTs are unnecessary for fibroblast locomotion in an oriented, three-dimensional extracellular matrix (ECM) (Schutze et al, 1991) or for rapid migration of tiny fish keratocytes (Euteneuer and Schliwa, 1984), or keratocyte fragments (Verkhovsky et al, 1999). Fibroblasts, however, require MTs (Gail and Boone, 1971;Vasiliev et al, 1970), specifically dynamic MTs (Liao et al, 1995), for spontaneous and wound-healing migration.…”
mentioning
confidence: 99%
“…29 These studies on Dictyostelium discoideum 28 and fibroblasts 29 suggest that polarization of the centrosome is not required for directional migration in three-dimensional gels. However, large-vessel ECs differ from fibroblasts because the cells migrate on a substratum that defines a luminal and an abluminal surface of the cell, and the cells migrate only in a two-dimensional plane.…”
Section: A Centrosome-dependent Reendotheualeationmentioning
confidence: 99%
“…28 Thus, in Dictyostelium discoideum the position of the centrosome is dependent on the conditions of migration and the nature of cell-cell adhesion. 28 In a study that used chicken embryo fibroblasts, 29 it was found that the centrosomes of cells grown on glass coverslips reoriented in the direction of cell migration, whereas In vitro large-wound re-endothelialization. Inhibition of centrosome redistribution by…”
Section: Hours Later Cells Were Double Stained To Localize F-actin (mentioning
confidence: 99%